2019
DOI: 10.1111/eth.12921
|View full text |Cite
|
Sign up to set email alerts
|

Spiders, microbes and sex: Bacterial exposure on copulatory organs alters mating behaviour in funnel‐web spiders

Abstract: Environmental microbes have the potential to be involved in nearly all behavioural processes. For example, mating systems where males use intromittent organs to transfer sperm to females represent a means by which environmental microbes collected by males can breach entry into females' body cavities during mating. However, the degree to which the acquisition of environmental microbes onto important sex structures alters courtship behaviours remains unknown. Here, we collected bacteria from the copulatory organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 59 publications
(86 reference statements)
1
3
0
Order By: Relevance
“…This may be because, in contrast to previous studies, in the case of S. nobilis only the protein products present in the mature sperm obtained from the spider pedipalps were used in the analysis. The detection of bacterial protein/peptides in this study is consistent with this, as spiders like S. nobilis use intromittent organs to transfer sperm to females, and environmental microbes are introduced into females during mating (Spicer et al, 2019).…”
Section: Of Clams Chickens and Spiderssupporting
confidence: 88%
“…This may be because, in contrast to previous studies, in the case of S. nobilis only the protein products present in the mature sperm obtained from the spider pedipalps were used in the analysis. The detection of bacterial protein/peptides in this study is consistent with this, as spiders like S. nobilis use intromittent organs to transfer sperm to females, and environmental microbes are introduced into females during mating (Spicer et al, 2019).…”
Section: Of Clams Chickens and Spiderssupporting
confidence: 88%
“…As we develop an understanding of the structural and functional diversity of reproductive microbiomes, more refined definitions may begin to emerge, with a narrower focus and more specialised to the biology of different systems. Such definitions might benefit from identifying the host and/or site of the microbiome (e.g., the human reproductive microbiome [7], the vaginal microbiome of primates [11], or the microbiome of copulatory organs of spiders [108]).…”
Section: Defining the Reproductive Microbiomementioning
confidence: 99%
“…Those that engaged in reproductive activity exhibited a significant reduction in lytic activity. These results suggest a down-regulation of immunity associated with the expression of reproductive behaviors, which could leave spiders more susceptible to sexually-transmitted microbes (Spicer et al 2019). found that the ingestion of bacteria as a juvenile leads to stronger immune responses in adult S. ochreata wolf spiders, but was also associated with decreased body condition and asymmetrical foreleg tufts, which is an important sexually-selected trait.…”
Section: Spider Biology Relevant To Parasitesmentioning
confidence: 79%
“…It is unlikely that exposure to cuticular bacteria alone can induce these changes, but none of these studies identified the route by which bacteria enter the host body after a topical application. Spicer et al (2019) applied a cocktail of cuticular bacteria onto A. pennsylvanica sex organs, and found that females who mated with males whose pedipalps were exposed to bacteria experienced reduced survivorship compared to females who had bacteria injected directly into the epigynum. Thus, the epigynum may not represent a potential route for the acquisition of environmental microbes but transfer from male intromittent organs (the embolus) warrants further study.…”
Section: Major Groups That Parasitize Spidersmentioning
confidence: 99%